Teaching Issues in an ESP Context and Course Design - BEN OUADAH SENOUCI, Khadidja (My University, 2017)
Teaching English for specific purposes has expanded and varied its fields to become a fundamental subject to be taught in the universities of their various departments. The research is conducted to deduce the difficulties faced by English language teachers when they attempt to provide ESP courses to first-year master students in the IT department of the year 2016/2017. It aims to show the learners' awareness and the awareness of English teachers to the needs and objectives of the ESP course. A triangular approach is adopted to collect both the quantitative and qualitative data needed for this research.
The Case Study: Tutors and 1st Year Master Student in Computer Science Department for the Academic Year 2016/2017
Keywords: Teaching of English for specific purposes; Master in Computer Science; Problems and solutions